Determinants of Access to Agricultural Subsidy and Perceived Subsidy Utilization Behavior in Sindhuli District, Nepal - Tiwari, Narayan Prasad (Journal of Agriculture and Forestry University, 2026)
Agricultural input subsidies (AIS) are considered an important tool for improving farm productivity and enhancing food security. Farmers’ perception influences participation, adoption behavior, and overall program outcomes. To identify the determinants of access to subsidy and the perceived subsidy utilization index, cross-sectional research was conducted at three local levels of Sindhuli Marin, Kamalmai, and Hariharpur Gadhi from September to December 2025. A total of 20 AIS beneficiaries and 20 non-beneficiaries were surveyed using a pretested interview schedule from each local level to comprise the total randomly selected sample of 120 households. Data analysis was done using a probit model to identify the determinants of access to subsidy and utilization behavior, and EFA, CFA, and regression techniques. Sociodemographic characteristics like the gender (β= -1.227, p=0.022) of the household head and family type (β=1.098, p=0.011) have a significant influence on access to subsidy. Institutional variables such as farmer visits to the extension office (β=-1.423, p=0.000), membership in cooperatives (β=0.852, p=0.032), and membership in farmers' groups (β=0.639, p=0.092) have a positive and significant influence on receiving subsidies. Behavioral variables derived from the Theory of Planned Behavior (TPB), such as attitude and subjective norms, have a positive and significant influence on receiving a subsidy. The explanatory variable, attitude toward subsidy effectiveness and governance, and perceived internal control, was a statistically significant determinant of subsidy utilization behavior. This study concludes that farmers' perception of subsidy differs among the subsidy receivers and non-receivers, and behavioral factors also determine the subsidy use. Policymakers should focus on easing the subsidy-receiving process and information dissemination, reducing complex paperwork to make the subsidy system more effective and ensure wider participation.